Game sense pedagogy for performance, participation and enjoyment - Light, Richard (Richard Lawrence); T&F eBooks (Milton Park, Abingdon, Oxon ; New York : Routledge, 2013)
"Game Sense is an exciting and innovative approach to coaching and physical education that places the game at the heart of the session. It encourages the player to develop skills in a realistic context, to become more tactically aware, to make better decisions, and to have more fun. Game Sense is a comprehensive, research-informed introduction to the Game Sense approach that defines and explores key concepts and essential pedagogical theory, and that offers an extensive series of practical examples and plans for using Game Sense in real teaching and coaching situations.The first section of the book helps the reader to understand how learning occurs and how this informs player-centred pedagogy, and explains the relationship between Game Sense and other approaches to Teaching Games for Understanding. The second section of the book demonstrates how the theory can be applied in practice, providing a detailed, step-by-step guide to using Game Sense in eleven sports, including soccer, basketball, field hockey and softball. No other book explores the Game Sense approach in such depth, or combines both the theory and innovative practical techniques. Game Sense is invaluable reading for all students of physical education or sports coaching, any in-service physical education teacher, or any sports coach working with children or young people. "--
1. Introduction -- 2. The development of Game Sense -- 3. Theorizing learning in and through Game Sense -- 4. Game Sense for physical education and sport coaching -- 5. Game Sense pedagogy -- 6. Assessing knowledge-in-action in team games -- 7. Touch rugby -- 8. Oztag -- 9. Australian football -- 10. Soccer -- 11. Field hockey -- 12. Basketball -- 13. Netball -- 14. Cricket (kanga) -- 15. Softball -- 16. Ultimate frisbee -- 17. Volleyball.
Includes bibliographical references (p. [229]-236) and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Physical education and training -- Study and teaching; Sports -- Study and teaching; Sports for children -- Study and teaching; Coaching (Athletics); Sports for children -- Coaching; Electronic books